Saudi Arabia women teachers' psychological capital towards work engagement / Aljaghthami Eman-Nafa, Noormala Amir Ishak - Aljaghthami, Eman-Nafa; Amir Ishak, Noormala (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
Education in Saudi Arabia is ranked at number 84 in the Global Competitiveness Report 2016 -2017. In Saudi Arabia, most female teachers work in segregated public or private schools for female students. Through past research, it was reported that in Saudi Arabia, the overall ratio of engaged employees in Saudi Arabia is lesser than the world's average rate. The study examined the link between psychological capital and work engagement of these women teachers. 414 questionnaires were obtained from Saudi women teachers from three main cities in Saudi Arabia-Jeddah, Riyadh and Dammam. The findings revealed that psychological capital has an influence on work engagement on Saudi women teachers and the Ministry of Education in Saudi needs to invest in further improving and developing their performance towards achieving its education goals and put the country at par with other countries of the same income level and cultural background.